A New Time-Based Algorithm for Positioning Mobile Terminals in Wireless Networks. (16th March 2008) - Martin-Escalona Martin-Escalona, Israel Israel; Barcelo-Arroyo Barcelo-Arroyo, Francisco Francisco
Abstract : This paper presents a positioning algorithm, named time of arrival to time difference of arrival (TOAD), which computes time-difference-of-arrival (TDOA) measurements from the messages that time-of-arrival (TOA) stations in sight exchange while their positioning processes are running. This study addresses the accuracy of the TOAD algorithm in two different environments: line-of-sight (LOS) and non-line-of-sight (NLOS). Simulation is used to set up a wireless network. The Gauss-Newton nonlinear least squares algorithm is used to compute the positions in both TOA and TOAD stations. Results indicate that the TOAD algorithm increases the root mean square error (RMSE) of the positioning error in LOS scenarios by 10 to 20% compared with the RMSE achieved by TOA. This drop in accuracy contrasts with the results for the NLOS scenarios. The RMSE of TOAD in such scenarios is at least 10% lower than that achieved by TOA. This result is specially important since this latter scenario is the most common. Consequently, this novel technique therefore improves the scalability and integrity of TOA techniques based on RTT, making it possible for the stations to position themselves without injecting traffic and with QoS figures close and most times better than that achieved by TOA.